Polyostotic Fibrous Dysplasia in a Six-year-Old Boy - Manevska, Nevena; Todorova-Stefanovski, Dushica; Bundovska Kocev, Smiljana; Stojanoski, Sinisha; Makazlieva, Tanja (Galenos Yayinevi, 2023)
Fibrous dysplasia (FD) is a rare congenital benign bone disease that manifests as a defect in the bone remodeling process, affecting the function, differentiation, and maturation of osteoblasts. This process is located in the bone marrow, where the normal marrow tissue is replaced with immature bone islands and fibrous stroma. The etiology is unclear so far, but it is known to be connected with a point mutation of the gene that encodes Gs α protein at the time of embryogenesis, and because of that, all of the affected somatic cells become dysplastic. It is important to determine whether the mutation occurred earlier in the process of embryogenesis so that there will be more mutant cells and the disease will appear in a more severe form. The clinical presentation of FD is variable, so there are plenty of potential differential diagnoses. The most common include Paget disease, non-ossifying fibroma, osteofibrous dysplasia, aneurysmal bone cyst, adamantinoma, giant cell tumor, fracture callus, and low-grade central osteosarcoma.
Altı Yaşındaki Erkek Çocukta Poliostotik Fibröz Displazi